Performance evaluation of OFDM in audio system for DAB: article / Mohd Fadzli Ismail - Ismail, Mohd Fadzli (2009)
This paper presents the analysis of OFDM technique with audio sound signals using as an input, with the objective to show the advantages of multi-carrier OFDM modulation method compared with single-carrier 16-QAM for application in Digital Video Broadcasting (DAB).Programs and algorithms were utilizing MATLAB R2006a and using GUI to show the output of a sounds signals received while at receiver after its being transmitted from Transmitter. The output results will show the quality of the audio signals graphically and in form of audio received. The programs as well as GUI can accurately distinguish the output results of the audio signals received that simulates by OFDM and 16-QAM methods.